2016
DOI: 10.5713/ajas.15.0980
|View full text |Cite
|
Sign up to set email alerts
|

Identification of loci affecting teat number by genome-wide association studies on three pig populations

Abstract: ObjectiveThree genome-wide association studies (GWAS) and a meta-analysis of GWAS were conducted to explore the genetic mechanisms underlying variation in pig teat number.MethodsWe performed three GWAS and a meta-analysis for teat number on three pig populations, including a White Duroc×Erhualian F2 resource population (n = 1,743), a Chinese Erhualian pig population (n = 320) and a Chinese Sutai pig population (n = 383).ResultsWe detected 24 single nucleotide polymorphisms (SNPs) that surpassed the genome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(48 reference statements)
1
14
1
Order By: Relevance
“…), lysine demethylase 6B ( KDM6B ) (Tang et al . ), Rap guanine nucleotide exchange factor ( RAPGEF1 ) (Verardo et al . ), secretory carrier membrane protein 2 ( SCAMP2 ) (Lee et al .…”
Section: Effect Of the Ssc5:60296617 Snp On Teat Number Traitsmentioning
confidence: 99%
“…), lysine demethylase 6B ( KDM6B ) (Tang et al . ), Rap guanine nucleotide exchange factor ( RAPGEF1 ) (Verardo et al . ), secretory carrier membrane protein 2 ( SCAMP2 ) (Lee et al .…”
Section: Effect Of the Ssc5:60296617 Snp On Teat Number Traitsmentioning
confidence: 99%
“…Wada et al 2000 ; Hirooka et al 2001 ; Rodríguez et al 2005 ; Bidanel et al 2008 ; Ding et al 2009 ; Hernandez et al 2014 ) or by applying genome‐wide association studies (GWAS) within breeds (e.g. Arakawa et al 2015 ; Rohrer & Nonneman 2017 ; Tang et al 2017 ; Lee et al 2019 ; van Son et al 2019 ). Results of these studies evidenced many different QTL affecting this trait and confirmed its polygenic nature.…”
Section: Introductionmentioning
confidence: 99%
“…Number of teats (NTE) in pigs is a highly heritable trait and shows considerable variation across breeds (8–21) (Rohrer and Nonneman, 2017) and also within breeds (e.g., 12–20 in Landrace) (Lopes et al, 2014). Several genome-wide association studies (GWAS) have shown that NTE is a polygenic trait influenced by many different quantitative trait loci (QTL) scattered over nearly all chromosomes of the pig genome (Duijvesteijn et al, 2014; Lopes et al, 2014; Arakawa et al, 2015; Verardo et al, 2016; Yang et al, 2016; Tang et al, 2017; Uzzaman et al, 2018). Among these, a QTL on Sus scrofa chromosome 7 (SSC7) has been identified showing a large effect on NTE in several commercial breeding lines and crosses (e.g., Duijvesteijn et al, 2014; Rohrer and Nonneman, 2017; Dall’Olio et al, 2018).…”
Section: Introductionmentioning
confidence: 99%